Effects on meat quality and black bone incidence of elevated dietary vitamin levels in broiler diets challenged with aflatoxin - Mota, M. M. (Animal, 2019)
Vitamins play an essential role in broiler nutrition. They are fundamental for normal metabolic and physiological process, and their requirements for poultry are not fixed and can be affected by multiple factors. In contrast, mycotoxins are a challenging issue because they hinder performance and the immune system. Vitamin supplementation above minimum requirements would permit improvement in productive potential, health, bone and meat quality in a situation of mycotoxin challenge. The objective of this study was to determine the influence of optimum vitamin nutrition in diets contaminated with aflatoxin in broilers from 1 to 44 days of age. A total of 1800 Cobb 500 male chicks were randomized to 15 sets of eight treatment groups, each containing 15 birds using a 2 × 2 × 2 factorial design (commercial vitamin levels and high vitamin levels, two levels of aflatoxin – 0 and 0.5 ppm with binder levels of 0 and 10 000 mg/kg). The mash diets were corn and soybean meal based, formulated according to commercial practices. Feed intake, weight gain and feed conversion were analyzed for birds from 1 to 44 days of age. To determine carcass characteristics (carcass yield, breast yield and leg yield) and black bone syndrome, two birds were slaughtered from each group at 45 days. Other analyses included breast tenderness, water loss by dripping and malonaldehyde concentrations. The results demonstrated that broilers that were fed high levels of vitamins showed better weight gain, feed conversion, carcass yield and breast yield than broilers that were fed diets with commercial vitamin levels (P < 0.05); also, broilers that were fed diets containing 0.5 ppm aflatoxin had lower weight gain, carcass yield and breast yield (P < 0.05). The use of 10 000 mg/kg of binder improved (P < 0.05) feed conversion throughout the rearing period. We conclude that aflatoxin negatively affects performance and carcass yield; however, feeding optimum vitamin nutrition improved these performance traits.